On the sources of business cycles: Implications for DSGE models - Michal Andrle; Jan Brůha; Serhat Solmaz (European Central Bank (ECB), 2017)
What are the drivers of business cycle fluctuations? And how many are there? By documenting strong and predictable co-movement of real variables during the business cycle in a sample of advanced economies, we argue that most business cycle fluctuations a re d riven b y o ne major factor. The positive co-movement of real output and inflation convincingly argues for a demand story. This feature - robust across time and space - provides a simple smell test for structural macroeconomic models. We propose a simple statistic that can compare data and models. Based on this statistic, we show that the recent vintage of structural economic models has difficulties replicating the stylized facts we document.
Keywords: C10; E32; E50; 330; Business cycle; demand shocks; dynamic principal component analysis; DSGE models